2017
DOI: 10.1246/cl.170440
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Size-controlled Rh Nanoparticles via Microwave-assisted Alcohol Reduction and Their Catalysis of CO Oxidation

Abstract: Size-controlled Rh nanoparticles stabilized by poly(vinylpyrrolidone) were quickly synthesized via alcohol reduction. Microwave-assisted synthesis in closed vessels allowed alcohols with low-to-high boiling points to be used as reductants under the same preparation conditions. Pure ethanol has not been used previously because its boiling point is lower than the temperature required for Rh 3+ reduction. Alcohols with relatively strong reduction ability were found to lead to smaller Rh nanoparticles. The ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…5F) as reducing agents and PVP as the stabilizer. 90 Polyalcohols with higher reduction potentials led to the formation of smaller Rh nanomaterials because of faster precursor reduction rate. 17 Aer incorporation of the obtained Rh nanomaterials (1 wt% Rh basis) onto g-Al 2 O 3 support by a wetimpregnation method, their catalytic activities were investigated in the CO oxidation reaction as a function of size.…”
Section: Controlling Shape Composition and Size In Noble-metal Npsmentioning
confidence: 99%
“…5F) as reducing agents and PVP as the stabilizer. 90 Polyalcohols with higher reduction potentials led to the formation of smaller Rh nanomaterials because of faster precursor reduction rate. 17 Aer incorporation of the obtained Rh nanomaterials (1 wt% Rh basis) onto g-Al 2 O 3 support by a wetimpregnation method, their catalytic activities were investigated in the CO oxidation reaction as a function of size.…”
Section: Controlling Shape Composition and Size In Noble-metal Npsmentioning
confidence: 99%
“…6 35) . It has also been reported that the electronic state of metal nanoparticles is markedly affected by particle size, especially for 2-10 nm particles 4),6), 11) . We are explor-J.…”
Section: Effect Of Particle Size On Catalytic Activity In Benzonitmentioning
confidence: 95%
“…The present study investigated five Rh samples with different particle sizes to elucidate the effect of particle size in more detail. Rh samples with different particle sizes were obtained simply by changing the alcohol reductant 11) . The use of stronger reductants (i.e., alcohols that are readily oxidized at low potential in linear sweep voltammetry, Fig.…”
Section: Effect Of Particle Size On Catalytic Activity In Benzonitmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as PGMs have relatively large redox potentials of ions/metal, to synthesize their NPs, chemical reduction methods that allow us to fine‐tune their structure can be adopted. To adjust the properties of PGM NPs, synthetic methods to precisely tune their size and/or morphology have been developed . Furthermore, metal NPs are well known to exhibit unique physical and chemical properties that are different from their bulk metals owing to the quantum size effect and the high surface‐to‐volume ratio .…”
Section: Introductionmentioning
confidence: 99%